1959
DOI: 10.1111/j.1476-5381.1959.tb00264.x
|View full text |Cite
|
Sign up to set email alerts
|

The Cardio‐active Principle in Spleen

Abstract: A substance has been demonstrated in acetone extracts of freeze‐dried spleen which had cardiotonic properties on isolated papillary muscles from the cat and perfused hearts of the cat and guinea‐pig. This activity of the extract could not be explained by the presence of choline, acetylcholine, histamine, 5‐hydroxytryptamine, adrenaline or noradrenaline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1964
1964
1984
1984

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…A second possibility is that the spleen releases a cardioactive substance. This cardiostimulatory activity of spleen extracts has been demonstrated in isolated papillary muscle preparations and isolated perfused hearts (Cobbin & Thorp, 1959). This cardiotonic factor called splentransin has been documented in several animal species and in extracts of human urine (Jackson et al, 1969;Spillert et al, 1980).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A second possibility is that the spleen releases a cardioactive substance. This cardiostimulatory activity of spleen extracts has been demonstrated in isolated papillary muscle preparations and isolated perfused hearts (Cobbin & Thorp, 1959). This cardiotonic factor called splentransin has been documented in several animal species and in extracts of human urine (Jackson et al, 1969;Spillert et al, 1980).…”
Section: Discussionmentioning
confidence: 92%
“…In addition to the above effects, studies have suggested that the spleen may have a direct effect upon myocardial contractility. In this regard, a cardiotonic factor isolated from animal spleens has been successful in stimulating isolated perfused hearts (Cobbin & Thorp, 1959;Jackson et al, 1969;Spillert et al, 1980). Also, cardiac output increases more in response to hypoxia in dogs with spleens intact compared to splenectomized dogs (Liang & Huckabee, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Cobbin and Thorp (36) found that the acetone fraction of splenic extracts contains a cardio-…”
Section: Metabolic Responses (Tables II and Iii)mentioning
confidence: 99%
“…The insensitivity of the receptor to autonomic agents allows a study of the direct effect of drugs on the membrane action potential without the influence of nervous factors. The presence of a cardio-active principle in freeze-dried extracts of ox spleen has been reported (Cobbin & Thorp, 1957), and later studies (Cobbin & Thorp, 1959, 1960Temple, Thorp & Gillespie, 1966) suggested that its activity on cat papillary muscle was attributable to a low molecular weight base, but not to histamine, choline, acetylcholine, catecholamines, 5-hydroxytryptamine, dopamine, tyramine or a number of other cardio-active amino-acids. More recently the substance was shown to be widely distributed in mammalian tissues (Jackson & Temple, 1969) and claimed to be fl-phenylethylamine (Jackson & Temple, 1970).…”
Section: Qdmentioning
confidence: 93%